Screening and characterization of a novel linear B-cell epitope on orf virus F1L protein - Zhang, Zhibang; Zhang, Xiaoyan; Feng, Kang; Ba, Shufan; Yang, Taotao; Gong, Jinxiang; Yang, Ziyin; Zhang, Hong; Sun, Zilong; Li, Pengcheng (Frontiers in Microbiology, 2024)
Background: Orf, also known as contagious ecthyma (CE), is an acute, contagious zoonotic disease caused by the orf virus (ORFV). The F1L protein is a major immunodominant protein on the surface of ORFV and can induce the production of neutralizing antibodies.The prokaryotic expression system was used to produce the recombinant F1L protein of ORFV, which was subsequently purified and used to immunize mice.Positive hybridoma clones were screened using an indirect enzyme-linked immunosorbent assay (ELISA). The reactivity and specificity of the monoclonal antibody (mAb) were verified through Western blot and indirect immunofluorescence (IFA). The linear antigenic epitope specific to the mAb was identified through Western blot, using truncated F1L proteins expressed in eukaryotic cells. A multiple sequence alignment of the ORFV reference strains was performed to evaluate the degree of conservation of the identified epitope.Results: After three rounds of subcloning, a mAb named Ba-F1L was produced.Ba-F1L was found to react with both the exogenously expressed F1L protein and the native F1L protein from ORFV-infected cells, as confirmed by Western blot and IFA.The mAb recognized the core epitope 103 CKSTCPKEM 111 , which is highly conserved among various ORFV strains, as shown by homologous sequence alignment.The mAb produced in the present study can be used as a diagnostic reagent for detecting ORFV and as a basic tool for exploring the mechanisms of orf 2 pathogenesis. In addition, the identified linear epitope may be valuable for the development of epitope-based vaccines.